Book reviews - Zavadskas, Edmundas Kazimieras (Journal of Business Economics and Management, 2008)
OPTIMIZATION METHODS FOR A STAKEHOLDER SOCIETYReviewed book: Willem K. Brauers. Optimization Methods for a Stakeholder Society: A Revolution in Economic Thinking by Multi‐objective Optimization. Boston / Dordrecht / London: Kluwer Academic Publishers, 2004.First published online: 14 Oct 2010